Effects of sanding and spray coating on fluid flow - Muhammad Nur'Azmi Azehar (2018)
The growing resolve to combat climate change has pushed engineers to pursue energy efficiency like never before. For fluid flow in channels such as industrial pipelines, energy is unnecessarily lost through frictional drag. Researchers have found that hydrophobic channel surfaces reduce frictional drag in fluid flow due to their optimal surface microstructures and low surface energy. To mimic the superhydrophobic lotus leaves, artificial fabrication of a hydrophobic surface involves two steps – altering of the surface roughness to an optimal microstructure and lowering its surface energy level to reduce the molecular surface attraction to water. In this project, hydrophobic surfaces were fabricated via the combined methods of sanding and spray coating on two materials with contrasting surface properties - Teflon and aluminium. The combined method aims to greatly enhance hydrophobicity on any material, thus making it versatile and adaptable for various applications. This report analyzed the effects of the combined methods on the specimens’ hydrophobicity levels, surface roughness and frictional drag reduction in channels. 58 specimens were fabricated with varying surface roughness based on different sandpaper grits, with specimens having varying layers of the spray coat. Preliminary experiments were conducted to investigate the individual effects of sanding and spray coating based on their contact angles and surface microstructures. Out of 58 different specimens, the set of both Teflon and aluminium specimens sanded with 220 grit sandpaper and spray coated achieved superhydrophobicity by having the most optimal complex microstructures and exhibiting the best contact angles of approximately 166° to 169°. Conducting the main pressure drop experiment in a channel concluded with the best pressure drop reduction specimens also being those sanded with 220 grit sandpaper and spray coated. The results prove that there is a strong relation between the contact angle and drag reduction ability. Furthermore, the fully treated specimens of both materials exhibited similar levels of hydrophobicity, indicating that this combined method can potentially be applied on various materials to achieve consistent results.